Antioxidant and Anti-Inflammatory Activities of Coenzyme-Q10 and Piperine against Cyclophosphamide-Induced Cytotoxicity in HuH-7 Cells. (13th July 2022) - AL-Johani, Norah S.; Al-Zharani, Mohammed; Aljarba, Nada H.; Alhoshani, Norah M.; Alkeraishan, Nora; Alkahtani, Saad
Abstract : Cyclophosphamide (CP) alkylates DNA and RNA produce crosslinks that cause gene expression and protein synthesis inhibition to exert its anticancer effect. However, adverse effects of CP have restricted the CP application in cancer treatment. We investigate coenzyme-Q10 (Q10) and piperine (P) protective role on CP oxidant and inflammatory effect. HuH-7 cells were exposed to varying concentrations and combinations of Q10, P, and CP and evaluated intracellular ROS generation as well as inflammatory responses upon exposure. Our results showed Q10 and/or P suppressed both basal and CP-induced ROS generation without upsetting the balance in activities of SOD, catalase, and GSH levels. Analysis of proinflammatory cytokine gene expression showed that CP treatment alone only induced expression of IL-6β . However, coexposure of the cells to both Q10 and CP caused significant suppression of basal Cox-2 and TNF-α gene expression, while coexposure of the cells to CP and P with Co-Q10 suppressed basal IL-1β gene expression. Q10 also suppressed CP-induced expression of Cox-1 . P and CP suppressed basal expression of IL-6β and IL-12β, while P and Q10 suppressed CP-induced IL1-α gene expression. Taken together, both Q10 and P seem to be inhibiting NF κβ pathway to suppress CP-mediated inflammation. In conclusion, Q10 and/or P induced suppression of ROS generation mediated by CP and also suppressed CP-induced inflammation by inhibiting expression of specific inflammatory cytokine.